Effects of a periodized small-sided game training intervention on physical performance in elite professional soccer - Owen, A. L.; Wong, D. P.; Paul, D.; Dellal, A. (The Journal of Strength and Conditioning Research, 2012)
The present study examined the effects of periodized small-sided game (SSG) training intervention during a 4-week in-season break on the physical performance changes (i.e., speed, aerobic performance, and repeated sprint ability) within elite European soccer players. Fifteen, elite, male, professional players (age: 24.5 ± 3.45 years; height: 181.1 ± 5.78 cm; body mass: 78.7 ± 7.67 kg; VO2max: 54.88 ± 5.25 ml/kg/min) from a Scottish Premier League team participated in 7 separate SSG sessions (3 vs. 3 plus goalkeepers) of which games lasted for a 3-minute duration for the selected number of games (ranged from 5 to 11) increasing over the intervention period. To examine the effects of the SSG intervention on physical performance changes, pre- and posttesting sessions took place over a 2-day period (day 1: anthropometry and repeated sprint ability [RSA] assessments; day 2: running economy [RE] and blood lactate assessments). Results show that the 4-week SSG training intervention induced significant improvement in RSA as indicated by faster 10-m sprint time (p < 0.05, small effect), total sprint time (p < 0.05, medium effect), and smaller percentage decrement score (p < 0.05, medium effect). Furthermore, the SSGs also led to an improvement in RE as indicated through significantly reduced VO2 and heart rate at running speed 9, 11, and 14 km/h (all p's < 0.05, large effects). In conclusion, the present study demonstrates that implementing a periodized SSG training intervention during the 4-week in-season break is capable of improving elite-level soccer players' physical fitness characteristics. Being able to develop physical characteristics in conjunction to technical and tactical elements of the game, within a relatively short period, makes SSGs an appealing proposition for fitness coaches, players, and technical coaches alike.